Can't Leave You Now! Intimate Partner Violence under Forced Coexistence and Economic Uncertainty - Esther Arenas-Arroyo; Daniel Fernández-Kranz; Natalia Nollenberger (Institute of Labor Economics (IZA), 2020)
With the COVID-19 outbreak imposing stay at home and social distancing policies, warnings about the impact of lockdown and its economic consequences on domestic violence has surged. This paper disentangles the effect of forced coexistence and economic stress on intimate partner violence. Using an online survey data set, we find a 23% increase of intimate partner violence during the lockdown. Our results indicate that the impact of economic consequences is twice as large as the impact of lockdown. We also find a large increase of domestic violence when the relative position of the man worsens, especially in contexts where that position was already being threatened. We view our results as consistent with the male backlash and emotional cue effects.
Keywords: J12; I18; 330; intimate partner violence; lockdown; economic stress; COVID-19; coronavirus